2017
DOI: 10.1007/s11886-017-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemias and Cardiovascular Prevention: Tailoring Treatment According to Lipid Phenotype

Abstract: Evidence from genetic studies suggests that besides lowering low-density lipoprotein cholesterol, pharmacological reduction of triglyceride-rich lipoproteins, or lipoprotein(a) will reduce risk for coronary heart disease. Dyslipidemia, in particular hypercholesterolemia, is a common clinical condition and represents an important determinant of atherosclerotic vascular disease. Treatment decisions are currently guided by the causative lipid phenotype and the presence of other risk factors suggesting a very high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…These factors together support normal circulatory function and its adaptive response to adverse environmental challenges, disturbance of which can predispose to atherosclerosis (Kim et al, 2013; Lee et al, 2013). Factors leading to atherosclerosis include consumption of high-fat and cholesterol diet (Marir et al, 2013), dyslipidemia (Sanin et al, 2017), diabetes (Lehrke and Marx, 2017), chronic inflammation (Lee et al, 2018), genetic risk (Whayne, and Saha, 2019), lack of exercise (Yang J. et al, 2017), hypertension (Hurtubise et al, 2016), social stress (Meng et al, 2019), smoking and other unhealthy life-styles or environmental factors (Niemann et al, 2017). As shown in a cohort study in Mexico, the coronary risk factors observed were dyslipidemia (100%), hypertension (86%), obesity/overweight (75%), metabolic syndrome (71%), smoking (68%), and diabetes (58%) (Rettori et al, 2014).…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 99%
“…These factors together support normal circulatory function and its adaptive response to adverse environmental challenges, disturbance of which can predispose to atherosclerosis (Kim et al, 2013; Lee et al, 2013). Factors leading to atherosclerosis include consumption of high-fat and cholesterol diet (Marir et al, 2013), dyslipidemia (Sanin et al, 2017), diabetes (Lehrke and Marx, 2017), chronic inflammation (Lee et al, 2018), genetic risk (Whayne, and Saha, 2019), lack of exercise (Yang J. et al, 2017), hypertension (Hurtubise et al, 2016), social stress (Meng et al, 2019), smoking and other unhealthy life-styles or environmental factors (Niemann et al, 2017). As shown in a cohort study in Mexico, the coronary risk factors observed were dyslipidemia (100%), hypertension (86%), obesity/overweight (75%), metabolic syndrome (71%), smoking (68%), and diabetes (58%) (Rettori et al, 2014).…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 99%
“…Some types of treatment and prevention methods are available to address dyslipidemia and atherosclerosis, such as specific medicines, as well as the adoption of a healthy lifestyle, which includes an improvement in eating habits [ 60 ]. One of the reasons for changing these habits is to improve the quality of lipids consumed in the diet, involving recommendations to reduce SFAs, which are associated with the dyslidemia process because they cause an increase in LDL, which is due to a reduction in the production and activity of the LDLR gene, related to alter the hepatic metabolic processes and fatty acid biosynthesis [ 61 ].…”
Section: Dyslipidemiasmentioning
confidence: 99%
“…In this context, studies have been highlighting the empowering element that nutrition information in a food service setting has in allowing consumers to make healthy choices [ 12 , 13 ] to control the advance of chronic diseases [ 14 ]. Excess sodium and lipid consumption is a significant health problem that contributes to hypertension, diabetes, obesity and other chronic illnesses which are leading causes of death worldwide [ 11 , 15 , 16 , 17 ]. Although the studies show that nutritional information is the most critical strategy to induce healthier food choices, systematic reviews assessed the influence of menu-labeling on food choices and the studies verified that the only exposition of calorie/nutrients labeling in menus is not sufficient to promote healthier food choices [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%